Gerdes on the musical staff - Tello Malpartida, Aurelio (2023)
Federico Gerdes' corpus of musical works is made up of short, highly condensed scores with absolute control over the resources he uses. As part of the dossier dedicated to this musician, to commemorate the sesquicentennial of his birth and the seventieth anniversary of his death, ANTEC: Peruvian Journal of Musical Research, is releasing two scores that had been kept in manuscript form.